Hubungan Antara Kinerja Lingkungan, Pengungkapan Lingkungan dan Leverage terhadap Profitabilitas pada Perusahaan Food Andbeverage yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Erinda Aprilia Puspitasari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the relationship between environmental performance, environmental disclosure, and leverage on profitability in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. Profitability is measured using Return on Assets (ROA) and Return on Equity (ROE). The data used in this study were analyzed using IBM SPSS Statistics 22 with the Classical Assumption Test, Determination Coefficient Test, T test and F test to test the significance of the influence of independent variables on the dependent variable. The results of the T test show that environmental performance and leverage have a significant effect on profitability with a significance value <0.05, while environmental disclosure is .0.05 which means it is not significant. In addition, the F test shows that simultaneously, environmental performance, environmental disclosure, and leverage have a significant positive effect on profitability, with a significance value of 0.000 ˂ 0.05. Based on these results, the fourth hypothesis proposed in this study is accepted. This study provides implications that companies that pay attention to environmental performance and transparency in disclosing environmental information can increase their profitability, and proper leverage management also contributes to the company's financial sustainability. These findings are important for company management and investors to consider environmental sustainability aspects in strategic decision making.Keywords: Environmental Performance, Environmental Disclosure, Leverage, ProfitabilyThis study aims to analyze the relationship between environmental performance, environmental disclosure, and leverage on profitability in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. Profitability is measured using Return on Assets (ROA) and Return on Equity (ROE). The data used in this study were analyzed using IBM SPSS Statistics 22 with the Classical Assumption Test, Determination Coefficient Test, T test and F test to test the significance of the influence of independent variables on the dependent variable. The results of the T test show that environmental performance and leverage have a significant effect on profitability with a significance value <0.05, while environmental disclosure is .0.05 which means it is not significant. In addition, the F test shows that simultaneously, environmental performance, environmental disclosure, and leverage have a significant positive effect on profitability, with a significance value of 0.000 ˂ 0.05. Based on these results, the fourth hypothesis proposed in this study is accepted. This study provides implications that companies that pay attention to environmental performance and transparency in disclosing environmental information can increase their profitability, and proper leverage management also contributes to the company's financial sustainability. These findings are important for company management and investors to consider environmental sustainability aspects in strategic decision making.